2006
DOI: 10.1152/ajpheart.00489.2006
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin-induced diabetes progressively increases blood-brain barrier permeability in specific brain regions in rats

Abstract: This study investigated the effects of streptozotocin-induced diabetes on the functional integrity of the blood-brain barrier in the rat at 7, 28, 56, and 90 days, using vascular space markers ranging in size from 342 to 65,000 Da. We also examined the effect of insulin treatment of diabetes on the formation and progression of cerebral microvascular damage and determined whether observed functional changes occurred globally throughout the brain or within specific brain regions. Results demonstrate that strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
137
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 67 publications
10
137
1
1
Order By: Relevance
“…Increased BBB permeability was detected in patients with type II diabetes (Starr et al, 2003). Similarly, streptozotocin-induced diabetes in adult rats was associated with increases in permeability to small molecules, but similar to our findings, the changes were region specific with the largest changes occurring in the midbrain (Huber et al, 2006). The increases in BBB permeability in streptozotocin-induced diabetes appear to be related to a loss of tight junction proteins possibly resulting from increases in plasma matrix metalloproteinase activity and not from hyperglycemia alone (Hawkins et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Increased BBB permeability was detected in patients with type II diabetes (Starr et al, 2003). Similarly, streptozotocin-induced diabetes in adult rats was associated with increases in permeability to small molecules, but similar to our findings, the changes were region specific with the largest changes occurring in the midbrain (Huber et al, 2006). The increases in BBB permeability in streptozotocin-induced diabetes appear to be related to a loss of tight junction proteins possibly resulting from increases in plasma matrix metalloproteinase activity and not from hyperglycemia alone (Hawkins et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…39 Huber et al clearly showed time-dependent, molecular weight-dependent failure of barrier function using streptozotocin-induced diabetic rats. 40 In that study, they demonstrated that changes in BBB permeability were region C]-sucrose to evaluate the molecule size effect on BBB permeability. Interestingly, total albumin extravasation did not change in diabetic rats compared with controls, indicating that overall the BBB remained intact.…”
Section: Basic Experimentsmentioning
confidence: 98%
“…Metabolic abnormalities such as the long-lasting increase in blood glucose level, dyslipidemia, insulin resistance, hypertension and oxidative stress are common in diabetes mellitus. According to recent data, diabetes is a predisposing factor for Alzheimer disease (1), as older adults with type 2 diabetes sometimes develop cognitive impairments due to the impairment of insulin signaling and toxic accumulation of Amyloid Beta (Aβ) (2). The most affected parts are memory and mental processing speed, while cognitive skills such as attention, problem solving and general intelligence remain intact (3).…”
mentioning
confidence: 99%